Fouling behavior of colloidal particles in organic solvent ultrafiltration - Yin, Ziqiang (2022)
Membrane technology is increasingly becoming a promising alternative in the chemical and pharmaceutical industries, wherein organic solvents may form the continuous phase. Regarding the inevitable membrane fouling phenomenon, although the knowledge base is rich for feeds involving water, an analogous understanding for feeds involving organic solvents is limited. Accordingly, in this study, we systematically investigated the fouling behaviors of a model colloidal foulant (namely, silica) dispersed in water and five organic solvents (namely, methanol, ethanol, acetone, toluene and hexane) during ultrafiltration. The flux decline trends were clearly different. The XDLVO model and a fouling model were employed to extract mechanistic insights. Firstly, zeta potential alone was a poor indicator of the fouling extent. Secondly, solvents with high polarity (i.e., methanol, ethanol) had repulsive foulant-foulant and foulant-membrane interfacial interactions, which were beneficial in mitigating membrane fouling, leading to lesser flux decline and lower cake resistance. Thirdly, solvents with no or low polarity (i.e., n-hexane, toluene and acetone) had attractive interfacial interactions, which worsened membrane fouling. However, attractive foulant-foulant interaction was beneficial in augmenting shear-induced diffusion, which mitigated fouling. Fourthly, the fouling parameters extracted from the fouling model generally were lesser and greater respectively for the high-polarity and lower-polarity solvents, which agree with the interfacial interaction values and flux decline trends. The insights emanating from this study on membrane fouling in organic solvents are expected to be valuable in the design and operation of such emerging membrane-filtration systems.